PD-L1 pfeRNAs as blood-based predictors of treatment response of unresectable malignant pleural mesothelioma patients administered Durvalumab with cisplatin and pemetrexed as first-line therapy - Andrei Gurau; Suguru Yamauchi; Kaitlyn Ecoff; Kristen P. Rodgers; James R. Eshleman; Charles Conover Talbot Jr; Peng Huang; Joshua Choi; Patrick M. Forde; Valsamo Anagnostou; Malcolm Brock; Yuping Mei (Non-coding RNA Research)
Background: A new therapeutic avenue combining Durvalumab with cisplatin-pemetrexed (Durva-CP) has delivered a promising outcome for previously untreated patients with unresectable malignant pleural mesothelioma (MPM) in clinical trials. However, the limited patient response to Durva-CP needs predictors to select optimal candidates and monitor the developed resistance. Protein functional effector sncRNA (pfeRNA) reveals a fundamental mechanism underlying the regulation of protein activity. The common mechanisms underlying durvalumab, cisplatin, and pemetrexed indicate that PD-L1 pfeRNAs (PDLpfeRNAs) are key molecules that control the treatment response. Methods: We specified PDLpfeRNAs by sncRNA deep sequencing, confirmed their binding to PD-L1 by immunoprecipitation and reverse pull-down assays, and demonstrated their roles in controlling the interaction behaviors of PD1/L1 through quality-controlled drug development assays. Following the standards required for the CLIA-compliant LDT, we measured their expression levels in 60 plasma biospecimens from 30 unresectable MPM patients enrolled in the PrE0505 Phase II multicenter study. Using the Cox proportional hazards model and Kaplan-Meier analyses, we described their significance in predicting the treatment response of unresectable MPM patients administered Durva-CP as first-line therapy. Results: Two PDLpfeRNAs, PDLpfeRNAa and PDLpfeRNAb, were characterized, confirmed to bind to PD-L1, and identified to control the interaction behaviors of PD-1/L1. Their plasma relative expression levels (REL) demonstrated significant prognostic value for both overall survival (p = 0.0019) and progression-free survival (p = 0.019), and the association remained significant after adjusting for histological subtype (HR 2.59, 95 % CI: 1.00–6.70, p = 0.050) and age (HR 1.03, 95 % CI: 0.98–1.07, p = 0.269). Conclusions: Plasma PDLpfeRNAs are predictors of treatment response of unresectable MPM patients treated with Durva-CP as first-line therapy to select optimal candidates and monitor the developed resistance.